2020
DOI: 10.3390/medicina56050218
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Health of Nonagenarians in Southern Italy: A Descriptive Analysis from a Cross-Sectional, Home-Based Pilot Study of Exceptional Longevity (Cilento Initiative on Aging Outcomes or CIAO)

Abstract: Background and objectives: Nonagenarians and centenarians (NCs) are an extremely fragile population, particularly in regard to their physical and cognitive function. The aim of this study was to define the neurocognitive profiles among 29 NCs and their 49 younger cohabitants aged 50–75 years from The Cilento Initiative on Aging Outcomes (CIAO) Pilot study in the South of Italy that had provided initial hypotheses regarding positive psychological traits related to exceptional longevity. Materials and Methods: D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 57 publications
0
11
0
Order By: Relevance
“…Regarding Cilento area, Scelzo et al [14] who studied nonagenarians and centenarians in Cilento, showed that those who lived in the hilly rural area of the territory adopted specific lifestyles, such as hard work, love of the land, family, and religion, which allowed them to maintain mental well-being and made them particularly resilient and optimistic. Moreover, the study by Pizza et al [15] on Cilento nonagenarians also emphasized the importance of lifestyle, diet, but also individual personality factors. However, it is interesting to note that long-lived populations living in the buffer zone seem to be less protected.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding Cilento area, Scelzo et al [14] who studied nonagenarians and centenarians in Cilento, showed that those who lived in the hilly rural area of the territory adopted specific lifestyles, such as hard work, love of the land, family, and religion, which allowed them to maintain mental well-being and made them particularly resilient and optimistic. Moreover, the study by Pizza et al [15] on Cilento nonagenarians also emphasized the importance of lifestyle, diet, but also individual personality factors. However, it is interesting to note that long-lived populations living in the buffer zone seem to be less protected.…”
Section: Discussionmentioning
confidence: 99%
“…In this area, man has been able to integrate harmoniously with the forms of the landscape [45]. [14,15,44]. Our hypothesis is that some environmental indicators, such as altitude, climate, and rural hinterland may be protective factors for longevity.…”
Section: Description Of the Case Study: The Cilento Regionmentioning
confidence: 99%
“…The present investigation was born out of the Cilento Initiative on Aging Outcomes (CIAO) study (Scelzo et al, 2018). We have previously reported that, compared to their younger (age 50-75) cohabitants, people aged !90 exhibited better mental well-being, with resilience, optimism, religiosity, family bonds, and stubbornness (Scelzo et al, 2018), a healthier metabolic and cardiovascular profile (Daniels et al, 2019), and no significant differences in the laboratory assessment of oxidative stress and APOE genotype (Pizza et al, 2020). The people > 90 did not have severe cognitive impairment, and the prevalence of dementia was low.…”
Section: Introductionmentioning
confidence: 99%
“…31 These data suggest that genetics, Mediterranean lifestyle (diet and psychosocial habits), could be involved in maintaining this balance unaltered over time, allowing for healthier aging. 32 …”
mentioning
confidence: 99%
“…Cilentos’ nonagenarians seemed to have good cognitive status when compared to younger cohabitants aging 50–65 years, without significant differences in oxidative stress markers or apolipoprotein E (ApoE) genotype attributing these results to an optimal adherence to the MD, although other lifestyle factors and positive personality traits may also contribute to their healthy aging. 32 In this scenario a recent study attempted to identify genes/miRNAs involved in life span and health span in LLIs from Cilento. 54 In particular, the authors evaluating the circulating mononuclear cells (MNCs) transcriptome, found that both BPIFB4 andCXCR4 expression in MNCs were powerful classifiers of healthy aging in LLIs.…”
mentioning
confidence: 99%